Pengaruh Edukasi Terhadap Dukungan Keluarga Mengenai Keselamatan Lansia Di Rumah Di Sekolah Lansia Sibulan Kecamatan Sukajadi Kota Bandung - Mely Nursari Ningsih; Asri Handayani Solihin; Kuslan Sunandar (Sehat MasadaJurnal, 2023)
Elderly is someone who has reached the age of 60 years and over. The elderly are vulnerable to health and safety problems at home, such as falls (25%), pressure sores (10.8%), drug safety (3.577 times) more at risk than non-elderly, and psychosocial-related hazards (9.8%). One of the efforts that can be done is by providing education to raise family awareness of the importance of family support regarding the safety of the elderly at home. The purpose of the study was to identify the effect of education on family support regarding the safety of the elderly at home. This type of research is Quasi Experimental using a pretest-posttest one group design with a prospective technique. The research location is at the Sibulan Elderly School, Sukajadi District Bandung City. The total population is 70 people, with a sample size of 30 people using purposive sampling technique. Data collection using a support questionnaire. Data analysis using t test. The results showed that the family support before being given education with an average value of 73.57 and after being given education the average value became 79.30. So it can be concluded that there is a significant effect of education on family support regarding the safety of the elderly at home p-value (0.000<0.05). It is recommended that families seek information through print media, mass media or participate in counseling activities about family support regarding the safety of the elderly at home, especially information about the health of the elderly and related to drug use in the elderly.